Memantine Displays Antimicrobial Activity by Enhancing Escherichia coli Pathogen-Induced Formation of Neutrophil Extracellular Traps - Peng, Liang; Li, Li; He, Xiao-Long; Yu, Jing-Yi; Zeng, Zhi-Jie; Yang, Wei-Jun; Zhang, Bao; Zhang, Tie-Song; Cao, Hong; Huang, Sheng-He; Liu, Li-Qun (Frontiers in Cellular and Infection Microbiology, 2020)
Bacterial infection remains one of the leading causes of death worldwide due to the continuous rise of multiple antibiotic-resistant bacteria. Focusing solely on bacteria as the drug targets is a major limitation inherent in the conventional antibiotic therapy. Recently, host-directed therapies have become such an innovative approach to modulate the host defense system and the interplay of innate and adaptive immunity. Our previous studies showed that memantine (MEM), an α7 nAChR antagonist, could efficiently block multi-drug resistant Escherichia coli-caused bacteremia and meningitis in a mouse model. However, the underlying mechanisms that govern the antibacterial effects of MEM are still unknown. In this study, we demonstrated that MEM is able to significantly suppress E. coli infection by enhancing E. coli-induced formation and release of NETs in vitro and in vivo. MEM could promote the trapping and bactericidal activities of the polymorphonuclear neutrophils (PMNs) in a manner dependent on α7 nAChR, since knockdown of this receptor noticeably reduces the survival ability of bacteria in PMNs while MEM no longer affects the survival of bacteria in PMNs. Our results also showed that when the expression of S100A9, an antiseptic protein, is inhibited, pathogen survival rates in PMNs increase significantly. MEM reverses this effect in a concentration-dependent manner. MEM stimulates the production of MPO, S100A9, and DNA in PMNs and accelerates the release of depolymerized chromatin fibers into the extracellular space, suggesting the formation of NETs. Taken together, our data suggest that MEM effectively blocks bacterial infection through the promotion of the antibacterial function of NETs induced by E. coli.